Highly degradable porous melt-derived bioactive glass foam scaffolds for bone regeneration. (15th July 2017) - Nommeots-Nomm, Amy; Labbaf, Sheyda; Devlin, Aine; Todd, Naomi; Geng, Hua; Solanki, Anu K.; Tang, Hok Man; Perdika, Polytimi; Pinna, Alessandra; Ejeian, Fatemeh; Tsigkou, Olga; Lee, Peter D.; et al.
Graphical abstract: Abstract: A challenge in using bioactive melt-derived glass in bone regeneration is to produce scaffolds with interconnected pores while maintaining the amorphous nature of the glass and its associated bioactivity. Here we introduce a method for creating porous melt-derived bioactive glass foam scaffolds with low silica content and report in vitro and preliminary in vivo data. The gel-cast foaming process was adapted, employing temperature controlled gelation of gelatin, rather than the in situ acrylic polymerisation used previously. To form a 3D construct from melt derived glasses, particles must be fused via thermal processing, termed sintering. The original Bioglass® 45S5 composition crystallises upon sintering, altering its bioactivity, due to the temperature difference between the glass transition temperature and the crystallisation onset being small. Here, we optimised and compared scaffolds from three glass compositions, ICIE16, PSrBG and 13–93, which were selected due to their widened sintering windows. Amorphous scaffolds with modal pore interconnect diameters between 100–150 µm and porosities of 75% had compressive strengths of 3.4 ± 0.3 MPa, 8.4 ± 0.8 MPa and 15.3 ± 1.8 MPa, for ICIE16, PSrBG and 13–93 respectively. These porosities and compressive strength values are within the range of cancellous bone, and greater than previously reported foamed scaffolds. Dental pulp stem cells attached to the scaffold surfaces during in vitro culture and were viable. In vivo, the scaffolds were found to regenerate bone in a rabbit model according to X-ray micro tomography imaging. Statement of Significance: This manuscript describes a new method for making scaffolds from bioactive glasses using highly bioactive glass compositions. The glass compositions have lower silica content that those that have been previously made into amorphous scaffolds and they have been designed to have similar network connectivity to that of the original (and commercially used) 45S5 Bioglass. The aim was to match Bioglass' bioactivity. The scaffolds retain the amorphous nature of bioactive glass while having an open pore structure and compressive strength similar to porous bone (the original 45S5 Bioglass crystallises during sintering, which can cause reduced bioactivity or instability). The new scaffolds showed unexpectedly rapid bone regeneration in a rabbit model.